Peran PT. Bank SUMUT Syariah KCP Stabat Dalam Mendorong Usaha Kecil Dan Menengah - Nadila Sabila; Abdullah Sani; Anjur Perkasa Alam (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2022)
This research aims to find out the role of PT. Bank SUMUT Syariah KCP Stabat in developing Small and Medium Enterprises. The research method used in this research is a qualitative research method that is descriptive with an empirical approach. The results of the study explained that the role of PT. Bank SUMUT Syariah KCP Stabat in developing Small and Medium Enterprises is by developing human assets, developing capital assets and developing social assets to Small and Medium Enterprises. The obstacles faced are: lack of public knowledge about PT. Bank SUMUT Syariah KCP Stabat, accustomed to using conventional banks, lack of public attention to usury practices. The solutions carried out are: making advertisements, brochures, stamps and banners, often visiting areas around Stabat District, making customers as partners. The Positive Impact felt by Small and Medium Enterprises helps local communities in developing the economy, the community feels an increase in income, increased production, quality, quality and assets.